Peranan KKN sebagai Perwujudan Penerapan Pengetahuan Tentang Pengolahan Jagung kepada Masyarakat Desa Bleberan, Kabupaten Gunungkidul - Prasetyo Jati, Didit Gunawan (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2021)
Kuliah Kerja Nyata (KKN) is an educational activity in higher education as a form of academic activity related to community service programs. One of the villages is the location for organizing KKN , namely Bleberan Village, Playen District, Gunungkidul, D.I. Yogyakarta. The result of food crops with the largest commodity in this village is corn. This can be seen as a big enough potential for the people of Bleberan Village. One of the products that is very likely to be produced from the corn plant is food products. Easy-to-cultivate corn plants also allow rural communities to carry out the processing process independently. Therefore, the role of KKN as a manifestation of the application of knowledge about corn processing is important for the people of Bleberan Village. It is intended that the villagers can further develop and maximize the processing of corn and economical commercial value that can help build the economy in the Bleberan Village. The method used in this journal is qualitative research. The method of collecting data sources used is using secondary data collection methods collected via the internet, documentation of the conversations of the author's team through online means such as Whatsapp groups and Microsoft Teams, as well as references from other sources.